2017
DOI: 10.1053/j.gastro.2016.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Choline Kinase α Mediates Interactions Between the Epidermal Growth Factor Receptor and Mechanistic Target of Rapamycin Complex 2 in Hepatocellular Carcinoma Cells to Promote Drug Resistance and Xenograft Tumor Progression

Abstract: We found levels of CHKA to be increased in human HCCs compared to nontumor tissues, and increased expression to be associated with tumor aggressiveness and reduced survival times of patients. Overexpression of CHKA in HCC cell lines increased their invasiveness, resistance to EGFR inhibitors, and ability to form metastatic tumors in mice by promoting interaction of EGFR with mechanistic target of rapamycin complex 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 42 publications
(37 reference statements)
1
48
1
1
Order By: Relevance
“…However, only EDI3 affected cell migration, indicating that this ratio is not predictive of migratory capacity. Interestingly, our findings differ from those of previous studies where silencing CHKA decreased motility and invasion (9)(10)(11)(12). In two studies (9,10), the authors reported reduced proliferation, but no direct effect on apoptosis, or on MAPK and PI3K/Akt signaling pathways, as published by others after CHKA inhibition in other cell lines (30)(31)(32)(33).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, only EDI3 affected cell migration, indicating that this ratio is not predictive of migratory capacity. Interestingly, our findings differ from those of previous studies where silencing CHKA decreased motility and invasion (9)(10)(11)(12). In two studies (9,10), the authors reported reduced proliferation, but no direct effect on apoptosis, or on MAPK and PI3K/Akt signaling pathways, as published by others after CHKA inhibition in other cell lines (30)(31)(32)(33).…”
Section: Discussioncontrasting
confidence: 99%
“…In two studies (9,10), the authors reported reduced proliferation, but no direct effect on apoptosis, or on MAPK and PI3K/Akt signaling pathways, as published by others after CHKA inhibition in other cell lines (30)(31)(32)(33). Furthermore, a recent study describing a role for CHKA in migration observed no direct effect on proliferation (12). Altogether, the role of CHKA in processes such as migration and proliferation requires further evaluation and may be cell type and context dependent.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The lung metastases assay was performed as previously reported (Lin et al, 2017). Briefly, six mice in the experiment group were injected intravenously with 1 9 10 6 tumor cells suspended in phosphate-buffered saline via the lateral tail vein, while six mice in the control group were injected intravenously with the same volume phosphate-buffered saline via the lateral tail vein.…”
Section: Lung Metastases Assay In Vivomentioning
confidence: 99%
“…However, those anti-EGFR agents have not been proved positive evaluation in hepatocellular carcinoma (HCC) despite the expression of EGFR is commonly high [4][5][6]. Lin et al reported that the anti-EGFR drug resistance in HCC is caused by the promoted interaction of EGFR with mTORC2, this shows that the complex signaling pathways is the main reason of drug resistance in liver cancer cells [7]. At present, the unique international recognized drug could benefit HCC patients is Sorafenib.…”
Section: Introductionmentioning
confidence: 99%